A Comparative Study of Group Cohesion between University and National Handball Male Players: A Comparative Study of Group Cohesion in Handball: University vs. National Players (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Handball is a very popular sport which involves many socializing characteristics that influencesthe overall game situations. In those type of socializing aspects group cohesion plays dominating role inhandball. In this study researcher wants to compare the group cohesion levels of national and Universityplayers. The data for this study gathered by the researcher through Brawley and widener‟s questionnairewhich assess the team cohesion of players. The data of 30 handball players were suitable for theevaluation. Researcher finds that team Cohesion aspects of AGT-T of national handball players arebetter than the university level handball players as well as Team cohesion aspects ATG-T of nationalhandball player are lower than the university level handball players. Team cohesion aspects GI-T ofnational handball player are lower than the university level handball players and at last Team cohesionaspects GI-S of national handball player are lower than the university level handball players.